Transcriptome-Derived Ligand-Receptor Interactome of Major PitNET Subgroups - Batchu, Sai; Diaz, Michael Joseph; Patel, Aashay; Reddy, Akshay; Lucke-Wold, Brandon (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction Pituitary neuroendocrine tumors (PitNETs) are rare skull base tumors which can impart significant disability owing to their locally invasive potential. To date, the gamut of PitNET subtypes remains ill-understood at the ligand-receptor (LR) interactome level, potentially limiting therapeutic options. Here, we present findings from in silico analysis of LR complexes formed by PitNETs with clinical presentations of acromegaly, Cushing's disease, high prolactin production, and without symptoms of hormone hypersecretion.Methods Previously published PitNET gene expression data was acquired from ArrayExpress. These data represented all secretion types. LR interactions were analyzed via a crosstalk score approach.Results Cortisol (CORT) ligand was significantly involved in tumor-to-tumor signaling across all PitNET subtypes but prolactinomas, which evidenced active CORT depletion. Likewise, CCL25 ligand was implicated in 20% of the top LR complex interactions along the tumor-to-stroma signaling axis, but silent PitNETs reported unique depletion of the CCL25 ligand. Along the stroma-to-tumor signaling axis, all clinical PitNET subtypes enriched stromal vasoactive intestinal polypeptide ligand interactions with tumor secretin receptor. All clinical PitNET subtypes enriched stromal DEFB103B (human β-defensin 103B) ligand interactions with stromal chemokine receptors along the stroma-to-stroma signaling axis. In PitNETs causing Cushing's disease, immune checkpoint ligand CD274 reported high stromal expression, and prolactinomas reported low stromal expression. Moreover, prolactinomas evidenced distinctly high stromal expression of immune-exhausted T cell response marker IL10RA compared with other clinical subtypes.Conclusion Relative crosstalk score analysis revealed a great diversity of LR complex interactions across clinical PitNET subtypes and between solid tumor compartments. More data are needed to validate these findings and exact clinical importance.
Keywords: PitNET; clinical subtype; Cushing's disease; acromegaly; ligand-receptor interactions; relative crosstalk score